2004
DOI: 10.1021/ja049436v
|View full text |Cite
|
Sign up to set email alerts
|

CO Oxidation on Aun/TiO2 Catalysts Produced by Size-Selected Cluster Deposition

Abstract: Planar model catalysts were prepared by deposition of size-selected gold clusters containing up to seven atoms on rutile TiO2 (110). Molecular oxygen is observed to bind inefficiently to the surface, probably at oxygen vacancies, and some oxygen also appears to bind to the gold clusters. Stable CO binding is observed atop gold for catalysts prepared by Au and Au2 deposition, but not for larger Aun. CO oxidation activity is strongly dependent on cluster size, with Au7-prepared samples >50 times more reactive th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
311
2
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 342 publications
(329 citation statements)
references
References 14 publications
13
311
2
1
Order By: Relevance
“…The unique activities of highly dispersed nanosized Au particles on oxide surfaces [1][2][3][4][5][6][7][8][9][10][11][12][13][14]42 are found to strongly correlate with the Au particle size; for example, the highest turnover frequency (TOF, reaction rate per surface Au site per second) occurs at a particle size of ∼3 nm. A model catalytic system, Au/TiO 2 (110), was used to investigate this unusual catalytic phenomenon under realistic reaction conditions.…”
Section: Active Au Catalysts: From Nanoparticles To Ordered Thin Filmsmentioning
confidence: 99%
“…The unique activities of highly dispersed nanosized Au particles on oxide surfaces [1][2][3][4][5][6][7][8][9][10][11][12][13][14]42 are found to strongly correlate with the Au particle size; for example, the highest turnover frequency (TOF, reaction rate per surface Au site per second) occurs at a particle size of ∼3 nm. A model catalytic system, Au/TiO 2 (110), was used to investigate this unusual catalytic phenomenon under realistic reaction conditions.…”
Section: Active Au Catalysts: From Nanoparticles To Ordered Thin Filmsmentioning
confidence: 99%
“…This is well-recognized, as can be seen even just from the publications on catalytic properties of clusters toward the reaction of CO oxidation Arenz et al 2006;Metiu 2006, 2008;Haruta and Date 2001;Heiz et al 1999;Kaden et al 2009;Landman et al 2007;Lee et al 2004;Lopez and Norskov 2002;Molina and Hammer 2005;Remediakis et al 2005;Sanchez et al 1999;Tang and Henkelman 2009;Valden et al 1998;Yoon et al 2005;Yoon et al 2012;Zhai et al 2010;Zhang and Alexandrova 2013). Indeed, many corner and edge sites and the availability of dangling orbitals for potential substrate binding, high strain for higher reactivity, and tunability of the electronic structure of clusters via their size, composition, and the environment all point at their potential to be good catalysts.…”
Section: Clusters In Catalysis Clusters Are Natural Suspects For Havmentioning
confidence: 93%
“…Anderson et al (Kaden et al 2009;Lee et al 2004) address the electronic structure -catalytic property dependences explicitly. They prepared size-selected clusters of Pd and Au deposited on TiO 2 (110), and measured their catalytic activity toward the reaction of CO oxidation as a function of cluster size (Figure 14).…”
Section: Clusters In Catalysis Clusters Are Natural Suspects For Havmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, many studies have shown that under controlled environments (ultrahigh vacuum) the catalytic performance of these model systems can be modified by the size [7][8][9][10] and chemical composition of the active centres (nanoparticles/clusters) [11,12] as well as the nature of the support materials. [13][14][15] However, also essential to the creation of more efficient catalyst materials is their stability and catalytic performance under more practical conditions, factors which may also vary significantly during the course of the reaction.…”
Section: Introductionmentioning
confidence: 99%